The Effect of Ca(OH)2 Concentration and Drying Time on Yam Bean Dried Candied Quality - Maria Goretty Manik; Linda Masniary Lubis; Sentosa Ginting (Jurnal Rekayasa Pangan dan Pertanian, 2016)
The aim of this research was to determine the effect of Ca(OH)2 concentration and drying time yam bean dried candied quality. This research was conducted in August until September 2015 in Food Chemical Analysis Laboratory, Agriculture Faculty, North Sumatera, Medan. This research was using factorial Completely Randomized Design with two factors, i. e: Ca(OH)2 concentration (S) : (0; 0,2%; 0,4%; 0,6%; 0,8%) and drying time combination (P) (8 hours; 10 hours; 12 hours). The analyzed parameters were moisture content, vitamin C content, total soluble solid, crude fiber content, ash content, score valueof colour, texture and hedonic value of colour, taste  and texture. The results showed that Ca(OH)2 concentration had highly significant effect on vitamin C content, score test of color,  texture, and hedonic test of texture, and had no effect to moisture content  and hedonic test of taste.The drying time combination had highly significant effect on moisture content, vitamin C content, total soluble solid, crude fiber content, ash content, score value of colour and texture, and had no effect on hedonic value of colour and texture. The interaction of the two factors had highly significant effect on score value of colour, texture and hedonic value of texture. Ca(OH)2 concentration of 0,4% and drying time of 12 hours were the best treatment and acceptable. The best dried candied bengkuang had a low antioxidant activity with the of IC50 value of 101-150 bpj. Keywords : Ca(OH)2 concentration, dried candied, drying time, yam bean.